Solid Waste Management Plan for Ayubia National Park - Farkhanda Fayyaz; Saeeda Yousaf; Anis Safir; Samiullah Memon; Mahwish Ahmed Alvi; Mohamed Lamin Sesay; Bai-Bureh O'Bai Kamara (Indus Journal of Social Sciences, 2025)
This study aims to evaluate the solid waste management scenario of Ayubia National Park and proposes a management plan. Due to lack of a proper mechanism for disposing of solid trash, all rubbish created is thrown away or publicly deposited in parks by visitors, residents, hotels, and restaurants. According to an evaluation 58.1% of the population disposes of their waste in the accessible public bins. Despite this, many people bemoan the lack of public bins in light of the large population. However, 32.6% of respondents said that there aren't enough public garbage cans in their area. Approximately 18.6% of the surveyed said they get rid of their solid waste in small spaces within their homes, 7% in public spaces, 7% areas close to national parks, and 2.3% in restroom lanes. During the solid waste characterization procedure in the field, it was found that some solid waste may be repurposed as an input into the cement industry. Here's an illustration of the circular economy in action. It is advised to establish an integrated solid waste management strategy for ANP based on information obtained from surveys and observations, which includes the 3Rs rule to protect the park, reduce the cost and benefit the environment.